Preparation process and application of honeycomb activated carbon with self-cleaning function

By modifying titanium dioxide with cobalt and nickel and combining with bamboo chip activated carbon, honeycomb activated carbon with self-cleaning function was prepared, which solved the problem of poor degradation of volatile organic compounds in the prior art, and achieved the use of pollutants such as formaldehyde efficient degradation and air purification effect.

CN118904292BActive Publication Date: 2025-02-11龙岩市华研活性炭科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411412184.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-11
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove volatile organic compounds, especially formaldehyde, from indoor air, which is a serious hazard to human health.

Method used

Honeycomb activated carbon with self-cleaning function was prepared by surface modification of titanium dioxide with cobalt and nickel and mixed with bamboo chip activated carbon and additives. The material degrades volatile organic matter through photocatalytic action and enhances its degradation ability to formaldehyde by modifying the combination of titanium dioxide and additives.

Benefits of technology

The efficient degradation of volatile organic compounds, especially formaldehyde, has achieved significantly improved the air purification effect, and through the reinforcement of modified titanium dioxide, the durability and self-cleaning function of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to a preparation process and application of honeycomb activated carbon with self-cleaning function, belonging to the technical field of activated carbon. The present invention discloses a honeycomb activated carbon with self-cleaning function, and the specific preparation method is as follows: (1) bamboo chips are carbonized by heating, and bamboo chips carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred and mixed, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chips activated carbon; (2) titanium dioxide is surface modified to obtain modified titanium dioxide; (3) modified titanium dioxide, bamboo chips activated carbon and auxiliary agents are mixed, impregnated at room temperature, and then made into a honeycomb shape using a mold, and hardened, baked in an oxygen-free environment, washed with water and dried to obtain honeycomb activated carbon with self-cleaning function. Titanium dioxide is surface modified with cobalt and nickel, which enhances the degradation of volatile organic compounds by activated carbon. Therefore, the present invention can prepare honeycomb activated carbon with self-cleaning function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon, and relates to a preparation process and application of honeycomb activated carbon with self-cleaning function. Background Art

[0002] Volatile organic compounds (VOCs) are a type of substance that is harmful to the human body and the environment during production activities, such as outdoor industrial production, traffic emissions, and indoor painting and printing. Most of the current decoration materials contain pollutants such as formaldehyde (HCHO). Formaldehyde is highly harmful and has a long release cycle. When the cumulative release exceeds a certain threshold, it will cause indoor air pollution and seriously endanger human health.

[0003] At present, the pore size distribution and surface functional groups of activated carbon are used to treat pollutants such as formaldehyde, which has the advantages of easy availability of materials and convenient operation. Studies have shown that TiO2 is loaded into activated carbon and irradiated with light of a certain wavelength to produce active substances participating in the reaction, degrading formaldehyde into CO2 and H2O, which has the effect of purifying the air. In addition, TiO2 is non-toxic, safe, green, and has a high photocatalytic efficiency. It is recognized as an ideal material for photocatalytic degradation of indoor pollutants such as formaldehyde. However, the spectral response range of TiO2 is narrow, and it is necessary to improve the photon utilization efficiency and photocatalytic activity by means of metal ion and non-metal ion doping. Summary of the invention

[0004] The present invention relates to a preparation process and application of honeycomb activated carbon with self-cleaning function, belonging to the technical field of activated carbon. The present invention discloses a honeycomb activated carbon with self-cleaning function, and the specific preparation method is as follows: (1) bamboo chips are carbonized by heating, and bamboo chips carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred and mixed, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chips activated carbon; (2) titanium dioxide is surface modified to obtain modified titanium dioxide; (3) modified titanium dioxide, bamboo chips activated carbon and auxiliary agents are mixed, impregnated at room temperature, and then made into a honeycomb shape using a mold, and hardened, baked in an oxygen-free environment, washed with water and dried to obtain honeycomb activated carbon with self-cleaning function. Titanium dioxide is surface modified with cobalt and nickel, which enhances the degradation of volatile organic compounds by activated carbon. Therefore, the present invention can prepare honeycomb activated carbon with self-cleaning function.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A preparation process of honeycomb activated carbon with self-cleaning function, the preparation method of honeycomb activated carbon comprising the following steps:

[0007] (1) Bamboo chips are heated and carbonized, and bamboo chip carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chip activated carbon for standby use;

[0008] (2) stirring cobalt acetate tetrahydrate and nickel acetate tetrahydrate in deionized water until dissolved to obtain a mixed solution;

[0009] (3) treating the nano-titanium dioxide by ultrasonic treatment in anhydrous ethanol, and then drying it. The product after cooling is the pretreated nano-titanium dioxide;

[0010] (4) stirring and mixing the mixed solution with the pretreated nano-titanium dioxide, performing solid-liquid separation when no more bubbles appear in the solution, heating and drying the solid, then introducing nitrogen, heating and keeping the temperature, and cooling to room temperature to obtain modified titanium dioxide;

[0011] (5) Modified titanium dioxide, bamboo chip activated carbon and additives are mixed, impregnated at room temperature, and then made into a honeycomb shape using a mold, hardened, anaerobic baked, washed with hot water and dried, and finally impregnated with a binder and dried to obtain a honeycomb activated carbon with self-cleaning function.

[0012] Furthermore, in the step (1), the temperature and time of the carbonization are 200-250° C. and 30-60 min respectively, the mesh size of the sieve is 100-300 mesh, the solid-liquid ratio of the bamboo shavings carbon powder to the phosphoric acid solution is 1-5:8-10 g / mL, the mass fraction of the phosphoric acid solution is 40-45%, and the activation temperature and time are 220-260° C. and 15-20 min respectively.

[0013] Furthermore, in the step (2), the solid-liquid ratio of the total amount of cobalt acetate tetrahydrate and nickel acetate tetrahydrate to deionized water is 2.5-15:50 nmol / mL, wherein the mass ratio of cobalt acetate tetrahydrate to nickel acetate tetrahydrate is 1:1.

[0014] Furthermore, in the step (3), the solid-liquid ratio of nano-titanium dioxide to anhydrous ethanol is 1-3:50 g / mL, the ultrasonic treatment time is 5-10 min, and the drying temperature and time are 50-60° C. and 15-20 min, respectively.

[0015] Furthermore, in step (4), the mass ratio of the mixed liquid to the pretreated nano-titanium dioxide is 2-3:1, the temperature and time of the solid heating and drying are 50-60°C and 20-30min respectively, the temperature and time of the insulation are 300-350°C and 120-150min respectively, and the heating rate is 2°C / min.

[0016] Furthermore, the mass ratio of the (5) modified titanium dioxide, bamboo chip activated carbon and the auxiliary agent is 0.01-0.03:1:1-3, wherein the auxiliary agent is composed of a phosphoric acid solution and a sulfuric acid solution in a mass ratio of 50:0.5-5, wherein the mass fraction of the phosphoric acid solution is 25% and the mass fraction of the sulfuric acid solution is 40%.

[0017] Furthermore, the immersion time in step (5) is 1-2h, the hardening temperature and time are 100-200°C and 30-60min respectively, the anaerobic baking temperature and time are 200-300°C and 120-150min respectively, and the hot water temperature is 60-80°C.

[0018] Furthermore, in the step (5), the binder is composed of silica sol and ethanol solution in a volume ratio of 1:1, wherein the mass fraction of the ethanol solution is 70%, and the immersion time is 30-60s.

[0019] Furthermore, the honeycomb activated carbon with self-cleaning function is applied in the field of air purification.

[0020] Beneficial effects of the present invention:

[0021] 1. Cobalt and nickel modify the surface of titanium dioxide, capture charge carriers, promote the separation of photogenerated electron-hole pairs, and provide captured charges for the redox reaction on the titanium dioxide surface as active reaction sites, thereby enhancing the degradation of volatile organic compounds by activated carbon;

[0022] 2. Using silica sol mixed with ethanol as a binder can effectively reinforce the modified titanium dioxide in the activated carbon, and the binder itself exists in a very fine form and will not affect the pore structure and surface area of ​​the activated carbon. Therefore, the durability of the honeycomb activated carbon with self-cleaning function is improved. DETAILED DESCRIPTION

[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0024] Example 1

[0025] A preparation process of honeycomb activated carbon with self-cleaning function, the preparation method of honeycomb activated carbon comprising the following steps:

[0026] (1) Bamboo chips are heated and carbonized, and bamboo chip carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chip activated carbon for standby use;

[0027] (2) stirring cobalt acetate tetrahydrate and nickel acetate tetrahydrate in deionized water until dissolved to obtain a mixed solution;

[0028] (3) treating the nano-titanium dioxide by ultrasonic treatment in anhydrous ethanol, and then drying it. The product after cooling is the pretreated nano-titanium dioxide;

[0029] (4) stirring and mixing the mixed solution with the pretreated nano-titanium dioxide, performing solid-liquid separation when no more bubbles appear in the solution, heating and drying the solid, then introducing nitrogen, heating and keeping the temperature, and cooling to room temperature to obtain modified titanium dioxide;

[0030] (5) Modified titanium dioxide, bamboo chip activated carbon and additives are mixed, impregnated at room temperature, and then made into a honeycomb shape using a mold, hardened, anaerobic baked, washed with hot water and dried, and finally impregnated with a binder and dried to obtain a honeycomb activated carbon with self-cleaning function.

[0031] The temperature and time of the carbonization in step (1) are 200° C. and 30 min respectively, the mesh size of the sieve is 100 mesh, the solid-liquid ratio of the bamboo shavings carbon powder to the phosphoric acid solution is 1:8 g / mL, the mass fraction of the phosphoric acid solution is 40%, and the activation temperature and time are 220° C. and 15 min respectively.

[0032] In the step (2), the solid-liquid ratio of the total amount of cobalt acetate tetrahydrate and nickel acetate tetrahydrate to deionized water is 2.5:50 nmol / mL, wherein the mass ratio of cobalt acetate tetrahydrate to nickel acetate tetrahydrate is 1:1.

[0033] In the step (3), the solid-liquid ratio of nano-titanium dioxide to anhydrous ethanol is 1:50 g / mL, the ultrasonic treatment time is 5 min, and the drying temperature and time are 50° C. and 15 min, respectively.

[0034] In the step (4), the mass ratio of the mixed solution to the pretreated nano-titanium dioxide is 2:1, the temperature and time of the solid heating and drying are 50°C and 20 minutes respectively, the temperature and time of the insulation are 300°C and 120 minutes respectively, and the heating rate is 2°C / min.

[0035] The mass ratio of the modified titanium dioxide, bamboo chip activated carbon and the auxiliary agent (5) is 0.01:1:1-3, wherein the auxiliary agent is composed of a phosphoric acid solution and a sulfuric acid solution in a mass ratio of 50:0.5, wherein the mass fraction of the phosphoric acid solution is 25% and the mass fraction of the sulfuric acid solution is 40%.

[0036] The immersion time in step (5) is 1 hour, the hardening temperature and time are 100° C. and 30 minutes respectively, the anaerobic baking temperature and time are 200° C. and 120 minutes respectively, and the hot water temperature is 60° C.

[0037] In the step (5), the binder is composed of silica sol and ethanol solution in a volume ratio of 1:1, wherein the mass fraction of the ethanol solution is 70%, and the immersion time is 30 seconds.

[0038] The honeycomb activated carbon with self-cleaning function is applied in the field of air purification.

[0039] The silica sol was purchased from: Whitt-HSD-8040.

[0040] Example 2

[0041] A preparation process of honeycomb activated carbon with self-cleaning function, the preparation method of honeycomb activated carbon comprising the following steps:

[0042] (1) Bamboo chips are heated and carbonized, and bamboo chip carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chip activated carbon for standby use;

[0043] (2) stirring cobalt acetate tetrahydrate and nickel acetate tetrahydrate in deionized water until dissolved to obtain a mixed solution;

[0044] (3) treating the nano-titanium dioxide by ultrasonic treatment in anhydrous ethanol, and then drying it. The product after cooling is the pretreated nano-titanium dioxide;

[0045] (4) stirring and mixing the mixed solution with the pretreated nano-titanium dioxide, performing solid-liquid separation when no more bubbles appear in the solution, heating and drying the solid, then introducing nitrogen, heating and keeping the temperature, and cooling to room temperature to obtain modified titanium dioxide;

[0046] (5) Modified titanium dioxide, bamboo chip activated carbon and additives are mixed, impregnated at room temperature, and then made into a honeycomb shape using a mold, hardened, anaerobic baked, washed with hot water and dried, and finally impregnated with a binder and dried to obtain a honeycomb activated carbon with self-cleaning function.

[0047] The temperature and time of heating carbonization in step (1) are 230° C. and 45 min respectively, the mesh size of the sieve is 200 mesh, the solid-liquid ratio of the bamboo shavings carbon powder to the phosphoric acid solution is 3:9 g / mL, the mass fraction of the phosphoric acid solution is 43%, and the activation temperature and time are 240° C. and 17 min respectively.

[0048] In the step (2), the solid-liquid ratio of the total amount of cobalt acetate tetrahydrate and nickel acetate tetrahydrate to deionized water is 7:50 nmol / mL, wherein the mass ratio of cobalt acetate tetrahydrate to nickel acetate tetrahydrate is 1:1.

[0049] In the step (3), the solid-liquid ratio of nano-titanium dioxide to anhydrous ethanol is 2:50 g / mL, the ultrasonic treatment time is 7 minutes, and the drying temperature and time are 55° C. and 17 minutes, respectively.

[0050] In the step (4), the mass ratio of the mixed solution to the pretreated nano-titanium dioxide is 2.5:1, the temperature and time of the solid heating and drying are 55°C and 25min respectively, the temperature and time of the insulation are 325°C and 135min respectively, and the heating rate is 2°C / min.

[0051] The mass ratio of the modified titanium dioxide (5), bamboo chip activated carbon and the auxiliary agent is 0.02:1:2, wherein the auxiliary agent is composed of a phosphoric acid solution and a sulfuric acid solution in a mass ratio of 50:0.5-5, wherein the mass fraction of the phosphoric acid solution is 25% and the mass fraction of the sulfuric acid solution is 40%.

[0052] The immersion time in step (5) is 1.5 hours, the hardening temperature and time are 150° C. and 45 minutes respectively, the anaerobic baking temperature and time are 250° C. and 135 minutes respectively, and the hot water temperature is 70° C.

[0053] In the step (5), the binder is composed of silica sol and ethanol solution in a volume ratio of 1:1, wherein the mass fraction of the ethanol solution is 70%, and the immersion time is 45 seconds.

[0054] The honeycomb activated carbon with self-cleaning function is applied in the field of air purification.

[0055] The silica sol was purchased from: Whitt-HSD-8040.

[0056] Example 3

[0057] A preparation process of honeycomb activated carbon with self-cleaning function, the preparation method of honeycomb activated carbon comprising the following steps:

[0058] (1) Bamboo chips are heated and carbonized, and bamboo chip carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chip activated carbon for standby use;

[0059] (2) stirring cobalt acetate tetrahydrate and nickel acetate tetrahydrate in deionized water until dissolved to obtain a mixed solution;

[0060] (3) treating the nano-titanium dioxide by ultrasonic treatment in anhydrous ethanol, and then drying it. The product after cooling is the pretreated nano-titanium dioxide;

[0061] (4) stirring and mixing the mixed solution with the pretreated nano-titanium dioxide, performing solid-liquid separation when no more bubbles appear in the solution, heating and drying the solid, then introducing nitrogen, heating and keeping the temperature, and cooling to room temperature to obtain modified titanium dioxide;

[0062] (5) Modified titanium dioxide, bamboo chip activated carbon and additives are mixed, impregnated at room temperature, and then made into a honeycomb shape using a mold, hardened, anaerobic baked, washed with hot water and dried, and finally impregnated with a binder and dried to obtain a honeycomb activated carbon with self-cleaning function.

[0063] The temperature and time of heating carbonization in step (1) are 250° C. and 60 min respectively, the mesh size of the sieve is 300 meshes, the solid-liquid ratio of the bamboo shavings carbon powder to the phosphoric acid solution is 5:10 g / mL, the mass fraction of the phosphoric acid solution is 45%, and the activation temperature and time are 260° C. and 20 min respectively.

[0064] In the step (2), the solid-liquid ratio of the total amount of cobalt acetate tetrahydrate and nickel acetate tetrahydrate to deionized water is 15:50 nmol / mL, wherein the mass ratio of cobalt acetate tetrahydrate to nickel acetate tetrahydrate is 1:1.

[0065] In the step (3), the solid-liquid ratio of nano-titanium dioxide to anhydrous ethanol is 3:50 g / mL, the ultrasonic treatment time is 10 min, and the drying temperature and time are 60° C. and 20 min, respectively.

[0066] In the step (4), the mass ratio of the mixed liquid to the pretreated nano-titanium dioxide is 3:1, the temperature and time of the solid heating and drying are 60°C and 30 minutes respectively, the temperature and time of the insulation are 350°C and 150 minutes respectively, and the heating rate is 2°C / min.

[0067] The mass ratio of the modified titanium dioxide (5), bamboo chip activated carbon and the auxiliary agent is 0.03:1:3, wherein the auxiliary agent is composed of a phosphoric acid solution and a sulfuric acid solution in a mass ratio of 50:5, wherein the mass fraction of the phosphoric acid solution is 25% and the mass fraction of the sulfuric acid solution is 40%.

[0068] The immersion time in step (5) is 2 hours, the hardening temperature and time are 200° C. and 60 minutes respectively, the anaerobic baking temperature and time are 300° C. and 150 minutes respectively, and the temperature of the hot water is 80° C.

[0069] In the step (5), the binder is composed of silica sol and ethanol solution in a volume ratio of 1:1, wherein the mass fraction of the ethanol solution is 70%, and the immersion time is 60 seconds.

[0070] The honeycomb activated carbon with self-cleaning function is applied in the field of air purification.

[0071] The silica sol was purchased from: Whitt-HSD-8040.

[0072] Comparative Example 1

[0073] On the basis of Example 3, a preparation process of honeycomb activated carbon with self-cleaning function is provided, wherein the preparation method of the honeycomb activated carbon comprises the following steps:

[0074] (1) Bamboo chips are heated and carbonized, and bamboo chip carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chip activated carbon for standby use;

[0075] (2) Titanium dioxide, bamboo chip activated carbon and additives are mixed and impregnated at room temperature, and then made into a honeycomb shape using a mold, hardened, baked in an oxygen-free environment, washed with hot water and dried, and finally impregnated with a binder and dried to obtain a honeycomb activated carbon with self-cleaning function.

[0076] The temperature and time of heating carbonization in step (1) are 250° C. and 60 min respectively, the mesh size of the sieve is 300 meshes, the solid-liquid ratio of the bamboo shavings carbon powder to the phosphoric acid solution is 5:10 g / mL, the mass fraction of the phosphoric acid solution is 45%, and the activation temperature and time are 260° C. and 20 min respectively.

[0077] The mass ratio of the titanium dioxide, bamboo chip activated carbon and auxiliary agent (2) is 0.03:1:3, wherein the auxiliary agent is composed of a phosphoric acid solution and a sulfuric acid solution in a mass ratio of 50:5, wherein the mass fraction of the phosphoric acid solution is 25% and the mass fraction of the sulfuric acid solution is 40%.

[0078] The immersion time in step (2) is 2 hours, the hardening temperature and time are 200° C. and 60 minutes respectively, the anaerobic baking temperature and time are 300° C. and 150 minutes respectively, and the hot water temperature is 80° C.

[0079] In the step (2), the binder is composed of silica sol and ethanol solution in a volume ratio of 1:1, wherein the mass fraction of the ethanol solution is 70%, and the immersion time is 60 seconds.

[0080] The honeycomb activated carbon with self-cleaning function is applied in the field of air purification.

[0081] The silica sol was purchased from: Whitt-HSD-8040.

[0082] Comparative Example 2

[0083] On the basis of Example 3, a preparation process of honeycomb activated carbon with self-cleaning function is provided, wherein the preparation method of the honeycomb activated carbon comprises the following steps:

[0084] (1) Bamboo chips are heated and carbonized, and bamboo chip carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chip activated carbon for standby use;

[0085] (2) stirring nickel acetate tetrahydrate in deionized water until dissolved to obtain a mixed solution;

[0086] (3) treating the nano-titanium dioxide by ultrasonic treatment in anhydrous ethanol, and then drying it. The product after cooling is the pretreated nano-titanium dioxide;

[0087] (4) stirring and mixing the mixed solution with the pretreated nano-titanium dioxide, performing solid-liquid separation when no more bubbles appear in the solution, heating and drying the solid, then introducing nitrogen, heating and keeping the temperature, and cooling to room temperature to obtain modified titanium dioxide;

[0088] (5) Modified titanium dioxide, bamboo chip activated carbon and additives are mixed, impregnated at room temperature, and then made into a honeycomb shape using a mold, hardened, anaerobic baked, washed with hot water and dried, and finally impregnated with a binder and dried to obtain a honeycomb activated carbon with self-cleaning function.

[0089] The temperature and time of heating carbonization in step (1) are 250° C. and 60 min respectively, the mesh size of the sieve is 300 meshes, the solid-liquid ratio of the bamboo shavings carbon powder to the phosphoric acid solution is 5:10 g / mL, the mass fraction of the phosphoric acid solution is 45%, and the activation temperature and time are 260° C. and 20 min respectively.

[0090] In the step (2), the solid-to-liquid ratio of nickel acetate tetrahydrate to deionized water is 15:50 nmol / mL.

[0091] In the step (3), the solid-liquid ratio of nano-titanium dioxide to anhydrous ethanol is 3:50 g / mL, the ultrasonic treatment time is 10 min, and the drying temperature and time are 60° C. and 20 min, respectively.

[0092] In the step (4), the mass ratio of the mixed liquid to the pretreated nano-titanium dioxide is 3:1, the temperature and time of the solid heating and drying are 60°C and 30 minutes respectively, the temperature and time of the insulation are 350°C and 150 minutes respectively, and the heating rate is 2°C / min.

[0093] The mass ratio of the modified titanium dioxide (5), bamboo chip activated carbon and the auxiliary agent is 0.03:1:3, wherein the auxiliary agent is composed of a phosphoric acid solution and a sulfuric acid solution in a mass ratio of 50:5, wherein the mass fraction of the phosphoric acid solution is 25% and the mass fraction of the sulfuric acid solution is 40%.

[0094] The immersion time in step (5) is 2 hours, the hardening temperature and time are 200° C. and 60 minutes respectively, the anaerobic baking temperature and time are 300° C. and 150 minutes respectively, and the temperature of the hot water is 80° C.

[0095] In the step (5), the binder is composed of silica sol and ethanol solution in a volume ratio of 1:1, wherein the mass fraction of the ethanol solution is 70%, and the immersion time is 60 seconds.

[0096] The honeycomb activated carbon with self-cleaning function is applied in the field of air purification.

[0097] The silica sol was purchased from: Whitt-HSD-8040.

[0098] Comparative Example 3

[0099] On the basis of Example 3, a preparation process of honeycomb activated carbon with self-cleaning function is provided, wherein the preparation method of the honeycomb activated carbon comprises the following steps:

[0100] (1) Bamboo chips are heated and carbonized, and bamboo chip carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chip activated carbon for standby use;

[0101] (2) stirring cobalt acetate tetrahydrate and nickel acetate tetrahydrate in deionized water until dissolved to obtain a mixed solution;

[0102] (3) treating the nano-titanium dioxide by ultrasonic treatment in anhydrous ethanol, and then drying it. The product after cooling is the pretreated nano-titanium dioxide;

[0103] (4) stirring and mixing the mixed solution with the pretreated nano-titanium dioxide, performing solid-liquid separation when no more bubbles appear in the solution, heating and drying the solid, then introducing nitrogen, heating and keeping the temperature, and cooling to room temperature to obtain modified titanium dioxide;

[0104] (5) Modified titanium dioxide, bamboo chip activated carbon and additives are mixed and impregnated at room temperature, and then made into a honeycomb shape using a mold, hardened, baked in an oxygen-free environment, washed with hot water and then dried to obtain a honeycomb activated carbon with self-cleaning function.

[0105] The temperature and time of heating carbonization in step (1) are 250° C. and 60 min respectively, the mesh size of the sieve is 300 meshes, the solid-liquid ratio of the bamboo shavings carbon powder to the phosphoric acid solution is 5:10 g / mL, the mass fraction of the phosphoric acid solution is 45%, and the activation temperature and time are 260° C. and 20 min respectively.

[0106] In the step (2), the solid-liquid ratio of the total amount of cobalt acetate tetrahydrate and nickel acetate tetrahydrate to deionized water is 15:50 nmol / mL, wherein the mass ratio of cobalt acetate tetrahydrate to nickel acetate tetrahydrate is 1:1.

[0107] In the step (3), the solid-liquid ratio of nano-titanium dioxide to anhydrous ethanol is 3:50 g / mL, the ultrasonic treatment time is 10 min, and the drying temperature and time are 60° C. and 20 min, respectively.

[0108] In the step (4), the mass ratio of the mixed liquid to the pretreated nano-titanium dioxide is 3:1, the temperature and time of the solid heating and drying are 60°C and 30 minutes respectively, the temperature and time of the insulation are 350°C and 150 minutes respectively, and the heating rate is 2°C / min.

[0109] The mass ratio of the modified titanium dioxide (5), bamboo chip activated carbon and the auxiliary agent is 0.03:1:3, wherein the auxiliary agent is composed of a phosphoric acid solution and a sulfuric acid solution in a mass ratio of 50:5, wherein the mass fraction of the phosphoric acid solution is 25% and the mass fraction of the sulfuric acid solution is 40%.

[0110] The immersion time in step (5) is 2 hours, the hardening temperature and time are 200° C. and 60 minutes respectively, the anaerobic baking temperature and time are 300° C. and 150 minutes respectively, and the temperature of the hot water is 80° C.

[0111] The honeycomb activated carbon with self-cleaning function is applied in the field of air purification.

[0112] 1. Performance Testing

[0113] According to the test method of Chinese patent CN103861421B, the adsorption test of volatile organic compounds was carried out on Example 3 and Comparative Examples 1-3. In addition, the honeycomb activated carbon with self-cleaning function prepared in Example 3 and Comparative Example 3 was placed for 3 months and 6 months, and the adsorption performance of volatile organic compounds was tested respectively, wherein the volatile organic compounds were a mixed gas of formaldehyde and ammonia.

[0114] The above test results are shown in Table 1.

[0115] Table 1 Test results

[0116]

[0117] As can be seen from Table 1, the removal rate of volatile organic compounds in Example 3 is greater than that in Comparative Examples 1-3, and the reduction in the removal rate of Example 3 after 3 and 6 months of placement is only 0.3%, while the removal rate of Comparative Example 3 is significantly reduced after 3 and 6 months of placement. The titanium dioxide added in Comparative Example 1 is not surface modified, and the substance itself is not ideal for the degradation of volatile organic compounds; in Comparative Example 2, nickel acetate tetrahydrate is used to modify the titanium dioxide surface, and its removal rate is worse than that of the modification of the titanium dioxide surface by nickel acetate tetrahydrate and cobalt acetate tetrahydrate in Example; Comparative Example 3 does not use a binder to reinforce the modified titanium dioxide in the activated carbon, and the modified titanium dioxide will fall off over time, causing the removal rate to decrease.

[0118] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A preparation process of honeycomb activated carbon with self-cleaning function, characterized in that: The preparation method of the honeycomb activated carbon comprises the following steps: (1) Bamboo chips are heated and carbonized, and bamboo chip carbon powder is obtained after screening, and then phosphoric acid solution is added and stirred, and then put into a furnace for heating to activate, and then cooled and taken out, washed with deionized water, and dried to obtain bamboo chip activated carbon for standby use; (2) stirring cobalt acetate tetrahydrate and nickel acetate tetrahydrate in deionized water until dissolved to obtain a mixed solution; (3) treating the nano-titanium dioxide by ultrasonic treatment in anhydrous ethanol, and then drying it. The product after cooling is the pretreated nano-titanium dioxide; (4) stirring and mixing the mixed solution with the pretreated nano-titanium dioxide, performing solid-liquid separation when no more bubbles appear in the solution, heating and drying the solid, then introducing nitrogen, heating and keeping the temperature, and cooling to room temperature to obtain modified titanium dioxide; (5) Modified titanium dioxide, bamboo activated carbon and additives are mixed, impregnated at room temperature, and then made into a honeycomb shape using a mold, hardened, anaerobic baked, washed with hot water and dried, and finally impregnated with a binder and dried to obtain a honeycomb activated carbon with a self-cleaning function; In the step (1), the temperature and time of heating carbonization are 200-250° C. and 30-60 min respectively, the mesh size of the sieve is 100-300 mesh, the solid-liquid ratio of the bamboo shavings carbon powder to the phosphoric acid solution is 1-5:8-10 g / mL, wherein the mass fraction of the phosphoric acid solution is 40-45%, and the activation temperature and time are 220-260° C. and 15-20 min respectively; In the step (2), the solid-liquid ratio of the total amount of cobalt acetate tetrahydrate and nickel acetate tetrahydrate to deionized water is 2.5-15:50 nmol / mL, wherein the mass ratio of cobalt acetate tetrahydrate to nickel acetate tetrahydrate is 1:1; In step (4), the mass ratio of the mixed solution to the pretreated nano-titanium dioxide is 2-3:1, the temperature and time of the solid heating and drying are 50-60°C and 20-30min, respectively, the temperature and time of the insulation are 300-350°C and 120-150min, respectively, and the heating rate is 2°C / min; In the step (5), the mass ratio of the modified titanium dioxide, the bamboo activated carbon and the auxiliary agent is 0.01-0.03:1:1-3, wherein the auxiliary agent is composed of a phosphoric acid solution and a sulfuric acid solution in a mass ratio of 50:0.5-5, wherein the mass fraction of the phosphoric acid solution is 25%, and the mass fraction of the sulfuric acid solution is 40%; The immersion time in step (5) is 1-2 hours, the hardening temperature and time are 100-200° C. and 30-60 minutes respectively, the anaerobic baking temperature and time are 200-300° C. and 120-150 minutes respectively, and the hot water temperature is 60-80° C.; In the step (5), the binder is composed of silica sol and ethanol solution in a volume ratio of 1:1, wherein the mass fraction of the ethanol solution is 70%, and the immersion time is 30-60s.

2. The preparation process of honeycomb activated carbon with self-cleaning function according to claim 1, characterized in that: In the step (3), the solid-liquid ratio of nano-titanium dioxide to anhydrous ethanol is 1-3:50 g / mL, the ultrasonic treatment time is 5-10 min, and the drying temperature and time are 50-60° C. and 15-20 min, respectively.

3. An application of honeycomb activated carbon with self-cleaning function prepared by the preparation process according to any one of claims 1 to 2, characterized in that: The honeycomb activated carbon with self-cleaning function is applied in the field of air purification.

Citation Information

Patent Citations

  • An air purifier

    CN103861421B

  • Water-resistant honeycomb activated carbon and preparation method thereof

    CN107126923A

  • Raw material for preparing activated carbon, activated carbon and removal method of VOCs (Volatile Organic Compounds)

    CN115608323A